(untitled) - Ford Foundation; Project on Social Welfare and the American Future.,Executive Panel (New York, N.Y., 1989)
This book presents the panel report of a project conducted by the Ford Foundation. The project examines the US social Welfare system, health and disability insurance, food and nutritional services and youth education and training programs
Keywords: Phúc lợi công cộng,Public welfare; Hoa Kỳ,United States